Increased myocardial sodium signal intensity in Conn's syndrome detected by 23Na magnetic resonance imaging. (10th October 2018) - Christa, Martin; Weng, Andreas M; Geier, Bettina; Wörmann, Caroline; Scheffler, Anne; Lehmann, Leane; Oberberger, Johannes; Kraus, Bettina J; Hahner, Stefanie; Störk, Stefan; Klink, Thorsten; Bauer, Wolfgang R; et al.
Abstract: Aims: Sodium intake has been linked to left ventricular hypertrophy independently of blood pressure, but the underlying mechanisms remain unclear. Primary hyperaldosteronism (PHA), a condition characterized by tissue sodium overload due to aldosterone excess, causes accelerated left ventricular hypertrophy compared to blood pressure matched patients with essential hypertension. We therefore hypothesized that the myocardium constitutes a novel site capable of sodium storage explaining the missing link between sodium and left ventricular hypertrophy. Methods and results: Using 23 Na magnetic resonance imaging, we investigated relative sodium signal intensities (rSSI) in the heart, calf muscle, and skin in 8 PHA patients (6 male, median age 55 years) and 12 normotensive healthy controls (HC) (8 male, median age 61 years). PHA patients had a higher mean systolic 24 h ambulatory blood pressure [152 (140; 163) vs. 125 (122; 130) mmHg, P  < 0.001] and higher left ventricular mass index [71.0 (63.5; 106.8) vs. 55.0 (50.3; 66.8) g/m 2, P  = 0.037] than HC. Compared to HC, PHA patients exhibited significantly higher rSSI in the myocardium [0.31 (0.26; 0.34) vs. 0.24 (0.20; 0.27); P  = 0.007], calf muscle [0.19 (0.16; 0.22) vs. 0.14 (0.13; 0.15); P  = 0.001] and skin [0.28 (0.25; 0.33) vs. 0.19 (0.17; 0.26); P  = 0.014], reflecting a difference of +27%, +38%, and +39%, respectively. Treatment of PHA resulted in significant reductions of the rSSI in the myocardium, calf muscle and skin by −13%, −27%, and −29%, respectively. Conclusion: Myocardial tissue rSSI is increased in PHA patients and treatment of aldosterone excess effectively reduces rSSI, thus establishing the myocardium as a novel site of sodium storage in addition to skeletal muscle and skin.